Physics beyond the Standard Model at ATLAS - Myaghov, Alexey (Array, 2008)
Summary: This report briefly reviews the potential of the ATLAS experiment to discover new phenomena beyond the Standard Model like new gauge bosons, extra dimensions and SUSY particles